Nicotine chewing gum as a substitute for smoking. Issue 6068 (23rd April 1977) - Russell, M A; Sutton, S R; Feyerabend, C; Cole, P V; Saloojee, Y
Abstract : The capacity of nicotine-containing chewing gum to produce plasma nicotine levels comparable to heavy cigarette smoking was tested in 21 subjects. On a fixed schedule of one piece of gum (4 mg nicotine) per hour, the average peak plasma nicotine concentration was 175-7 nmol/l (28-5 ng/ml) compared to 189-3 nmol/l (30-7 ng/ml) obtained from normal ad libitum smoking. Unpleasant side effects were common and in some cases plasma nicotine concentrations were two and even three times as high as with smoking; The chewing gum provided some satisfaction to all but four subjects, but its degree was not related to the concentration of plasma nicotine it produced, neither was there an inverse relation between the plasma nicotine concentration while taking the gum and the subjective sense of missing cigarettesmthis suggests that the capacity of the gum to act as a substitute for smoking is not necessarily related to its capacity to provide nicotine. Flexible dosage dictated by individual needs would probably lower the incidence of side effects and might secure closer approximation to smoking concentrations of plasma nicotine.